Healthy & Ready to Learn: Examining the Efficacy of an Early Approach to Obesity Prevention and School Readiness - Winter, Suzanne M.; Sass, Daniel A. (Journal of research in childhood education, 2011)
The collision of the childhood obesity epidemic with pressure to achieve high academic standards is of serious concern in the United States. Growing numbers of low-income, minority children face double jeopardy as alarming obesity rates further widen existing achievement gaps. Health and education disparities persist when children enter kindergarten lacking fundamental school readiness skills and are also at risk of obesity. The goal of this study was to address serious gaps in research by examining the efficacy of an innovative program, Healthy & Ready to Learn, an early approach to obesity prevention and promotion of school readiness. The study targeted low-income, predominantly Latino preschoolers who are particularly at risk of health and educational disparities. The pretest-posttest, quasi-experimental study involved 405 children, ages 3 to 5 years, enrolled in four matched Head Start centers. To ensure rigorous assessment, the study used a battery of objective and validated instruments as direct measures of child outcomes. Using multilevel modeling, several linear growth models were conducted with participant's growth at Level-1 (i.e., time) and subject-level variables at Level-2 (i.e., treatment, gender, age, & body mass index classification) for each outcome variable of interest. Results revealed statistically significant improvements in growth (i.e., height), gross motor skills, physical activity levels, and receptive language development when comparing the treatment and control conditions. These promising results suggest that the Healthy & Ready to Learn program has potential as an early approach to improve children's health and, simultaneously, enhance their trajectory toward better academic performance.